KARAKTERISASI FISIKOKIMIA CTMP BERTANDA TEKNESIUM-99m SEBAGAI RADIOFARMAKA PENYIDIK KANKER TULANG - Isti Daruwati; Misyetti Misyetti; Maula Eka Sriyani (Widyariset, 2009)
Radiopharmaceutical for bone cancer seeking was developed in variable phosphonate compound labeled with technetium-99m, formally pyrophosphate and diphosphonate compound. Either pyrophosphate or diphosphonate still unsatisfied to use as radiopharmaceuticals for bone seeking agent because the high accumulation in lever, muscle and blood. CTMP have higher affinity than others. The Physicochemical characterization of 99"Tc-CTMP has been conducted. The characteristic of labeled compound have to fulfill the criteria as the good radiopharmaceutical. The characteristic such as radiochemical purity, electric charge, lipophilicity, plasma protein binding, and hydroxy apatite binding. The results showed that the radiochemical purity greater than 95% (96,83 % ± 1,35), have a negative electric charge, lipophilicity -2,61, plasma protein binding 31,90 % ± 3,3, hydroxyl apatite binding 76,6% at 3 hours. The value ofhidroxy apatite binding was high, it showed CTMP have indicated a great potential as radiopharmaceutical for bone cancer seeking.